The paradox of immunosuppressants and COVID-19. Issue 4 (7th April 2022) - Cheng, Guang-Shing; Evans, Scott E.
For millions of people, taking immunosuppressive medication to control or prevent disease is a daily reality [1]. Rheumatological disease, inflammatory lung disease, organ transplantation and graft- versus -host disease are but a few of the immune dysregulation syndromes that may require short- or long-term immunosuppressive therapy (IST). Patients taking ISTs are frequently regarded as immunocompromised, sharing risks of increased infection susceptibility with cancer patients receiving chemotherapy, those with profound neutropenia from haematological malignancies, and individuals living with HIV. In the context of the immune-mediated respiratory failure associated with coronavirus disease 2019 (COVID-19), an apparent paradox arises: can ISTs both promote and protect against severe COVID-19? Lessons learned from a large registry analysis show worse COVID-19 outcomes for patients previously exposed to glucocorticoids https://bit.ly/306rNrk